PENGUJIAN TEGANGAN TEMBUS BOLAK BALIK PADA BAHAN ISOLASI MINYAK JARAK SEBAGAI ALTERNATIF MINYAK TRANSFORMATOR - Syarifasa, Arkananta; Dhofir, Moch.; Utomo, Teguh (Jurnal Mahasiswa TEUB, 2024)
The use of vegetable oil, especially castor oil as liquid insulation, needs to be proven by testing the breakdown voltage anddielectric strength of the oil as liquid insulation to predetermined standards. The test is to determine the breakdown voltageresistance and suitability of castor oil as an alternative liquid insulation for transformer oil in accordance with SPLN (StateElectricity Company Standards) and IEC (International Electrotechnical Commission) standards. The research method in thisstudy is analysis and direct measurement of the variables tested, namely the effect of heating with temperature variations on the breakdown voltage of castor oil. Testing of heating temperature variations on oil shows that there is an increase in the breakdown voltage value of castor oil after being given a directly proportional variation in heating temperature and experiencing a quite significant increase in breakdown voltage.  Keywordrs : Castor oil, Breakdown Voltage, Moisture Content, Permittivity, Conductivity